2022
DOI: 10.1002/er.7895
|View full text |Cite
|
Sign up to set email alerts
|

HF free greener Cl ‐terminated MXene as novel electrocatalyst for overall water splitting in alkaline media

Abstract: Summary Hydrogen and oxygen evolution through electrochemical water splitting is essential for effective and inexpensive production of hydrogen and oxygen, which depends on the development of economical, and extremely active electrocatalysts. Two‐dimensional (2D) nano‐laminated materials are imperious as electrocatalysts due to their phenomenal properties and extensive scope of applications. In this work, we report a greener way of synthesizing MXene without hydrofluoric acid (HF) treatment and demonstrated it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 63 publications
0
14
0
Order By: Relevance
“…Exploring high-performance electrocatalysts can effectively solve the above-mentioned issues. For example, Sarfraz et al reported the synthesis of Clterminated Ti 3 C 2 Cl 2 MXene via CuCl 2 etching of Ti 3 AlC 2 precursor in 2022, and Ti 3 C 2 Cl 2 MXene with obvious lamellar structure is then used as catalyst for water splitting in 1 M KOH solution [237]. Compared with Ti 3 C 2 T x MXene obtained by HF etching (HF-Ti 3 C 2 T x MXene), Ti 3 C 2 Cl 2 MXene possesses an enlarged interlayer spacing, more active sites and stable architecture.…”
Section: Overall Water Splittingmentioning
confidence: 99%
“…Exploring high-performance electrocatalysts can effectively solve the above-mentioned issues. For example, Sarfraz et al reported the synthesis of Clterminated Ti 3 C 2 Cl 2 MXene via CuCl 2 etching of Ti 3 AlC 2 precursor in 2022, and Ti 3 C 2 Cl 2 MXene with obvious lamellar structure is then used as catalyst for water splitting in 1 M KOH solution [237]. Compared with Ti 3 C 2 T x MXene obtained by HF etching (HF-Ti 3 C 2 T x MXene), Ti 3 C 2 Cl 2 MXene possesses an enlarged interlayer spacing, more active sites and stable architecture.…”
Section: Overall Water Splittingmentioning
confidence: 99%
“…Similarly, a greener synthesis route was also developed by Sarfraz et al , in which a Cl-terminated MXene was synthesized from the Ti 3 AlC 2 MAX phase via thermally reacting with a CuCl 2 salt at a high temperature in an inert environment, to successfully get rid of the HF. 100…”
Section: Structure Properties and Synthesis Of Mxenesmentioning
confidence: 99%
“…Similarly, a greener synthesis route was also developed by Sarfraz et al, in which a Cl-terminated MXene was synthesized from the Ti 3 AlC 2 MAX phase via thermally reacting with a CuCl 2 salt at a high temperature in an inert environment, to successfully get rid of the HF. 100 Importantly, etching conditions, including the HF concentration, etching temperature, and etching time, significantly influence the formation and properties of MXenes by adjusting the defects and surface terminations. 101,102 For example, a higher HF concentration (direct 48% HF etching) resulted in more -F surface terminations when compared with the amount of -O or -OH termination on Ti 3 AlC 2 , while a lower HF concentration (in situ HF-forming) produced Ti 3 AlC 2 with more -O terminations (Fig.…”
Section: Xinlong Linmentioning
confidence: 99%
“…[32][33][34][35][36][37] Transition metal carbides or nitrides or carbonitrides of two-dimensional (2D) materials, also known as MXene (M n+1 X n T x (n = 1, 2, 3), M = early transition metal, X = carbon and/or nitrogen, and T x = surface functional groups, such as ─O, ─OH, or ─F), are emerging as new candidates for catalyst supports owing to their unique properties such as high electrical conductivity, hydrophilicity, abundant surface functional groups, and stability. [38][39][40][41] Although MXene has recently been studied as an electrocatalyst for clean energy conversion reactions, [31,[42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57] its practical use is rarely feasible due to the large gap in reaching the catalytic activity levels of the related technologies. Meanwhile, many studies have obtained promising results when using MXene as the support material, including for OER catalysts.…”
Section: Introductionmentioning
confidence: 99%